2015
DOI: 10.1021/je501131j
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigations on the Reactive Extraction of Itaconic (2-Methylidenebutanedioic) Acid Using Trioctylamine (N,N-Dioctyloctan-1-amine)

Abstract: The paper presents the equilibrium distribution study of itaconic acid (also known as 2-methylidenebutanedioic acid, 0.615 mol·kg −1 ) between water and trioctylamine (TOA, 0.374 mol·kg −1 to 1.946 mol·kg −1 ) at 298 ± 0.1 K. The extract phase is prepared by varying the concentration of TOA and dissolving the same in four categories of solvents (alkane, ester, ketone and alcohol). The batch equilibrium results are presented in the form of loading ratio (Z), extraction efficiency (% E), and distribution coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…As previously reported, the amount of water transferred from the aqueous to the organic phase with the carboxylic acid is less than 5% and its effect on the value of K D is even smaller (35). This trend was consistently observed during the equilibrium steps in this study.…”
Section: Theorysupporting
confidence: 90%
“…As previously reported, the amount of water transferred from the aqueous to the organic phase with the carboxylic acid is less than 5% and its effect on the value of K D is even smaller (35). This trend was consistently observed during the equilibrium steps in this study.…”
Section: Theorysupporting
confidence: 90%
“…Reactive extraction of dicarboxylic acids has been shown to be applicable for various dicarboxylic acids, e.g. malonic acid [15][16][17], glutaric acid [18], succinic acid [15][16][17][19][20][21][22][23], fumaric acid [15][16][17], malic acid [18,24], maleic acid [15][16][17][18], itaconic acid [25][26][27] and cis,cismuconic acid (CCMA) [9]. However, the crucial step towards an applicable downstream process is not only the initial RE of the acid, but also a re-extraction (REEX) of the acid from the organic phase leading to the pure acid in an aqueous phase for further processing.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the formation of the third phase can be prevented if the polarity of the organic phase is increased by the addition of a polar modifier (1‐dodecanol within this study) . Besides preventing a third phase, the polarity of the organic phase has an influence on the RE conversion . The three most promising amines D‐C8, T‐C6, and T‐C8 were chosen for optimization of amine and modifier concentration under consideration of increased conversion ( X RE, IA > 0.90 for pure IA from water) and the prevention of a third phase (Table ).…”
Section: Resultsmentioning
confidence: 92%
“…, using the amine extractant mixture Aliquat 336. Aşçi and İnci , Uslu and Datta , and Kaur and Elst investigated RE of IA with the triamine tri‐ n ‐octylamine (T‐C8, or mixtures containing T‐C8) as extractant using bio‐incompatible organic solvents. Within the mentioned studies, RE was shown to be applicable for IA and hence offers a solid starting point for the presented integrated process development approach.…”
Section: Introductionmentioning
confidence: 99%